Intasc Standard Cores: Raising Students’ English Modality Competence - Muliani Muliani (Lingua Cultura, 2016)
This research aimed at raising the students’ modality competence with the implementation of a teaching model which was called as Interstate New Teachers Assessment and Support Consortium (INTASC) model that covering ten standards. It was expected that this research could give numerous contribution in teaching English, particularly in teaching English Modality where the problem found was that the students got difficulty in using modal verbs regarding both tense and aspect in which consequently would affect the communicative competence of the students. In the form of Research and Development, this research was carried by means of implementing validated instrument and 10 modules in the small and large scale assessments that involving 50 students in the small scale assessment and 80 students in the large-scale assessment. Standard 1-2 dealt with the students’ need and diversity of learning while standard 3-7 dealt with various instructions teaching the content knowledge regarding the use of English modality. Furthermore, standard 8-10 dealt with summative assessment, reflection, and professional development. Eventually, it is found that the level of learning of the students raise supported by the data that 94% of the level of learning can be achieved by the students while it was only 6% of the modality expressions cannot be used properly. It can be noted that this teaching model can assist the students in achieving the modality competence by having a very well-sequenced procedures of teaching in which this teaching model starts from considering the prior knowledge, the need, and the students’ diversity before creating further instructions regarding the content knowledge where the modality competence is the main goal to achieve.